The Household Income Potential Through Fish Farming In Abandoned Yard Ponds: A Case Study In Pasang Village, Enrekang Regency - Bahruddin Bahruddin; Rudy Arfah; Pidiya Aliman (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Fish ponds constructed by the village government in Pasang Village, Enrekang Regency, have not been optimally utilized and are largely abandoned. This study aims to analyze the potential for increasing household income through fish farming in abandoned yard ponds and to identify the supporting and inhibiting factors. A mixed methods approach, combining qualitative descriptive and quantitative analysis, was employed. Data were collected through interviews, questionnaires, and field observations conducted in Pasang Village, Maiwa District, Enrekang Regency. The findings indicate that revitalizing abandoned ponds has significant potential to enhance household income. However, several key constraints were identified, including limited capital, lack of technical knowledge in fish farming, and low community participation in sustainable pond management. Strengthening technical assistance and institutional support is essential to maximize the economic benefits of these underutilized resources.